Hepatic gene expression reveals functional diversity in indigenous chicken breeds - Bagiyal, Meena; Ahlawat, Sonika; Khatak, Sunita; Chhabra, Pooja; Sharma, Upasna; Arora, Reena; Sharma, Rekha; Parsad, Ram; Gera, Ritika (Journal of Livestock Biodiversity, 2025)
Poultry meat ranks among the most widely consumed sources of animal protein across the globe, with chicken breeds varying significantly in their genetic makeup, physiological traits, and adaptability. Indigenous breeds contribute not only to rural livelihoods but also possess valuable traits like disease resistance, stress tolerance, and superior meat quality. The liver, being central to metabolism and lipid regulation, plays a crucial role in determining growth, reproduction, and stress response in poultry. This study employed high-throughput RNA sequencing to compare hepatic transcriptomes of three distinct chicken breeds—Aseel, Kadaknath, and Punjab Brown, to identify gene expression patterns in each. Notably, genes such as APOV1 and VTG2 showed higher expression in Aseel, SPIA3, HMGCS1, and HSP90B1 in Kadaknath and DIO2 and EPAS1 in Punjab Brown. These differences reflect key roles in lipid metabolism, stress response, immunity and reproduction in these breeds, indicating distinct metabolic adaptations among the breeds.